Influence of Dietary Nitrate Supplementation on Physical Performance and Body Composition Following Offseason Training in Division I Athletes. (4th July 2022) - Townsend, Jeremy R.; Hart, Tricia L.; Haynes, James T.; Woods, Clint A.; Toy, Ann M.; Pihera, Bailey C.; Aziz, Marko A.; Zimmerman, Grace A.; Jones, Megan D.; Vantrease, William C.; Gonzalez, Adam M.
Abstract: Purpose: To determine the effects of dietary nitrate supplementation, in the form of red spinach extract (RSE), on adaptations to offseason training in collegiate athletes. Methods: Sixteen Division I male baseball athletes (20.5 ± 1.7y, 90.4 ± 0.5 kg) enrolled in this study and were randomized into a RSE ( n = 8) or placebo ( n = 8; PL) group. Athletes completed an 11-week resistance training program during the offseason, which consisted of 2-3 workouts per week of upper and lower-body exercises and baseball-specific training. Athletes consumed a RSE (2 g; 180 mg nitrate) or PL supplement daily for the entire offseason training program. Pre and post-training, all athletes underwent one-repetition maximum (1RM) strength testing for the bench press and completed a Wingate anaerobic cycle test (WAnT). Body composition analysis was completed via a 4-compartment model, as well as muscle thickness (MT) measurement of the rectus femoris (RF) and vastus lateralis (VL) via ultrasonography. Resting heart rate and blood pressure (BP) were also obtained. Separate repeated measures analyses of variance were used to analyze all data. Results: Significant ( p ≤ 0.05) main effects for time were observed for improved bench 1RM, fat-free mass, body fat percentage, RF MT, and VL MT. No significant group x time interactions ( p > 0.05) were found for any measure of performance, body composition, or cardiovascular health. However, a trend for improved peak power in the WAnT was observed ( p = 0.095; η 2 =0.200). Conclusions: These data suggest that daily RSE supplementation had no effect on performance, body composition, or cardiovascular measures in male Division I baseball players following offseason training.